His Grace, the Duke - Rath, Emily (Rath, Emily. Second sons, 2025)
When Rosalie Harrow found herself plunged into the middle of a house party of society ladies in pursuit of the hand of the Duke of Norland, though she was near destitute, she had no desire to be caged by marriage. Yet, by evening's end, she'd captivated not one, but three gentlemen . . .James Corbin, Viscount Finchley, has a dual mission. First, guarantee that his debaucherous brother, George, the Duke, goes through with his upcoming marriage. Second, ensure that his best friend, Burke, does not get married . . . at least not to the living, breathing gorgon that is Lady Olivia Rutledge. Burke is fully in agreement. Together with their friend, Lieutenant Renley, the gentlemen concoct an elaborate ruse to set Burke free. But as George's wedding day nears, secrets from the past emerge that threaten ruin upon each gentleman's future. Fortunately, it's Rosalie to the rescue . . . Rosalie has plans of her own, not only to save Burke from the altar, but to save Renley from the ghosts that haunt him-and to save James from himself. Meanwhile, to win her, each gentleman will try anything, risk anything, and be anything she needs. As for Rosalie, she can't help but wonder, why choose?